Genomic hotspots: localized chromosome gene expansions identify lineage-specific innovations as targets for functional biodiversity and predictions of stress resilience - Edsinger, Eric; Moroz, Leonid L. (Frontiers in Marine Science, 2024)
Functional and biodiversity genomics is essential for assessment and monitoring of planetary health and species-specific management in changing ecosystems. However, experimental knowledge of gene functions is limited to a few species, and dependencies on distantly related models. Combined with unrecognized degrees of lineage-specific gene family expansion, this means that traditional comparative methods are insufficient. Here, we introduce the concept of a hotspot, defined as innovations underlying the evolution of lineage-specific biology. We illustrate hotspots using molluscs having chromosome-scale genome assemblies and focus on heat-sensing TRPM channels and species living in environments of extreme heat stress (e.g., high intertidal and hydrothermal vent gastropods and bivalves). Integrating gene family, orthogroup, and domain-based methods with genomic hotspots (local homolog expansions on chromosomes), we show that conventional approaches overlook substantial amounts of species-specific gene family diversity due to limitations of distant homology detection. In contrast, local segmental duplications are often recent, lineage-specific genetic innovations reflecting emerging adaptions and can be identified for any genome. Revealed TRPM gene family diversification highlights unique neural and behavioral mechanisms that could be beneficial in predicting species’ resilience to heat stress. In summary, the identification of hotspots and their integration with other types of analyses illuminate evolutionary (neuro)genomic strategies that do not depend on knowledge from model organisms and unbiasedly reveal evolutionarily recent lineage-specific adaptations. This strategy enables discoveries of biological innovations across species as prospective targets for modeling, management, and biodiversity conservation.